Precursor frequencies for DNA-specific B lymphocytes in patients with systemic lupus erythematosus (SLE). - Schwab, J (1994)
Precursor frequencies for anti-DNA-secreting B cells were estimated in six healthy donors and 18 SLE patients with active and inactive disease. Precursors for IgG anti-dsDNA-secreting B cells were exclusively detected in SLE patients (73% of active patients and one inactive patient, 0.01-0.99% of IgG-producing B cells). These frequencies were in the same order of magnitude as frequencies of precursors for IgG anti-tetanus toxoid, which were detectable in three healthy volunteers after booster vaccination (0.07-0.8% of IgG-producing B cells), but not before (< 0.01%). Precursors for IgG anti-ss-DNA secreting B cells were observed in 33% of healthy donors and in 78% of SLE patients (0.01-0.32% of IgG-producing B cells). Only patient-derived IgG anti-DNA clones cross-reacted with (33%) or were monoreactive to dsDNA (12%). Precursors for IgM anti-DNA-secreting B cells were observed in healthy donors and SLE patients in comparable frequencies and with similar reactivities with ssDNA and dsDNA. Segregation analyses and sorting experiments showed that > 94% of clones secreting IgG anti-DNA were derived from in vivo sIgG+ B cells. sIgM+ B cells were induced to switch in vitro; however, only twice were cultures containing IgM and IgG anti-DNA antibodies observed under clonal conditions. In conclusion, our results indicate that precursor B cells for IgG anti-dsDNA in SLE patients are similarly selected and expanded as are precursor B cells specific for foreign antigens such as tetanus toxoid.